Emergency department organisation of critical care transfers in the UK. Issue 11 (21st October 2005) - Stevenson, A; Fiddler, C; Craig, M; Gray, A
Abstract : Objectives: Transport of the critically ill patient to or from the emergency department (ED) is a frequent occurrence. This study was designed to determine whether UK EDs currently have appropriate equipment, monitoring, staff training systems, and processes of care for transportation of the critically ill patient. Methods: A postal questionnaire regarding ED transfer patients was sent to 247 UK EDs, followed by repeat mailing and telephone follow up of non-responders. Results: In total, 139 EDs (56%) responded. An estimated 20–30 critically ill patients are transferred from and <20 are received by each ED annually. Processes of care are poorly developed; only 79 EDs (56%) have transfer guidelines available. Audit of transfers is ongoing in 59 EDs (42%), and critical incident reporting is ongoing in 122 (88%). There is a lack of immediately available transport equipment; for example, 17 EDs (12%) have no transport ventilator, 9 (6%) have no transport monitor, and 9 (6%) have no syringe pump. Transport equipment is invariably not standardised. Anaesthetic staff of specialist registrar (74 doctors; 53%) or senior house officer (36 doctors; 26%) grades carry out the majority of ED transfers accompanied by a D or E grade nurse. Both invariably have no formal transfer training. Conclusions: This study highlights inadequacies in provision of equipment and monitoring during interhospital transfer from the ED. Training and processes of care for transport of the critically ill are also suboptimum. Many departments are currently reviewing these processes to formalise and improve transfer training procedures and protocols.